From Punishment to Prevention: Disrupting the Prison Pipeline for At-Risk Youth - Ferawati, Ferawati; Fikranta, Atthyobi Muhammad (JURNAL LEGALITAS, 2025)
This study critically examines the effectiveness of addressing juvenile criminal cases through a predominantly repressive approach. Employing a normative legal research method, it draws upon statutory provisions of the Juvenile Criminal Justice System Act, relevant court decisions, and secondary legal literature to evaluate both regulatory intent and practical outcomes. While Indonesian law formally distinguishes the treatment of juvenile offenders from that of adults, findings indicate that implementation continues to generate significant adverse effects. These include enduring social stigma, psychological distress, and heightened risks of recidivism resulting from the imposition of custodial and other inappropriate penalties. Such outcomes underscore an urgent need to reassess the reliance on punitive measures in light of the state’s obligation to protect children as vulnerable legal subjects. The contribution of this research lies in advancing a preventive paradigm that prioritises family and community-based interventions. Specifically, it argues that empowering those closest to children particularly parents, caregivers, and educational institutions can mitigate criminogenic risks more effectively than punitive sanctions. By foregrounding preventive strategies, the study aligns juvenile justice with child protection principles and international best practices, thereby offering a model for reform that is both humane and sustainable. The novelty of this research rests in its proposition to operationalise prevention not merely through state mechanisms, but by maximising the protective role of family and immediate social environments. In doing so, it provides a fresh perspective for policymakers and legal practitioners seeking to reorient Indonesia’s juvenile justice system toward long-term rehabilitation and social reintegration.